2019
DOI: 10.1002/chem.201903670
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinoboration of Diazobenzene: Intramolecular FLP Synthon for PN2B‐Derived Heterocycles

Abstract: Phosphinoboration of diazobenzene with Ph2PBR′2 cleanly affords products of the form Ph2P(PhNNPh)BR′2 (2: R′2=catechol, cat; 4: R′2=phenanthrenediol, quin) and shows evidence of Ph2P(PhNNPh)Bpin 7 (pin: pinacol). The mechanism of these reactions was probed computationally and shown to proceed via intermediates involving a diazobenzene‐adduct of the boron center of the PB reagent. The resulting PNNB species 2 and 4 are shown to be frustrated Lewis pairs (FLPs). Despite the presence of weakly Lewis acidic boron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 53 publications
0
31
0
6
Order By: Relevance
“…Recent developments in phosphinoborations have focused on addition of PB species across C–heteroatom and N−N π‐bonds. In pioneering studies by Westcott and co‐workers, it was revealed that PBs Ph 2 P‐Bpin and Ph 2 P‐Bcat readily reacted with various aldehydes, ketones, and aldimines without any additives at room temperature to afford the corresponding 1,2‐addition products (Scheme a) .…”
Section: Methodsmentioning
confidence: 99%
“…Recent developments in phosphinoborations have focused on addition of PB species across C–heteroatom and N−N π‐bonds. In pioneering studies by Westcott and co‐workers, it was revealed that PBs Ph 2 P‐Bpin and Ph 2 P‐Bcat readily reacted with various aldehydes, ketones, and aldimines without any additives at room temperature to afford the corresponding 1,2‐addition products (Scheme a) .…”
Section: Methodsmentioning
confidence: 99%
“…11 Indeed, we have recently reported on the application of the BNNP FLPs derived from phosphinoborane addition to diazobenzene chemistry. 12 Acyl phosphines are used in industry as photoinitiators for radical-induced polymerization reactions 13 for automotive coatings, adhesives, latex composition kits, and various dental and orthodontic materials. 14 Known methodologies to such photoinitiators exploit pyrophoric, toxic, expensive reagents that are often difficult to handle.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, phosphino‐boranes, bearing the lower coordinated bond between a tricoordinated phosphorus and a tricoordinated boron atom (R 2 P–BR 2 ), have regained attention as they have been shown to activate H 2 and other small molecules and to coordinate to metals in a symmetric side‐on fashion . Moreover, phosphinoboronate esters [R 2 P–B(OR) 2 ] have shown phosphinoboration reactivity to double‐bond compounds and N‐heterocycles , . The different reactivities and properties of phosphine‐boranes, phosphino‐boranes and phosphino‐boronate esters depends on the coordination number of the phosphorus and boron atoms as well as the presence or absence of the phosphorus lone pair and boron vacant 2p orbital.…”
Section: Introductionmentioning
confidence: 99%